(untitled) (Tempo e Argumento, 2018)
Tradução do texto “The Future of Reading? Memories and Thoughts toward a Genealogical Approach”, de Hans Ulrich Gumbrecht, publicado na revista boundary 2 an international jornal of literature and culture, volume 41, número 3, 2014, p. 99–111